2016
DOI: 10.1016/j.jadohealth.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Teen Daughters and Their Mothers in Conversation: Identifying Opportunities for Enhancing Awareness of Risky Tanning Behaviors

Abstract: The incidence of melanoma has been increasing dramatically among teenage and young adult women over the past several decades. Despite a causal link between ultraviolet light exposure and melanoma, a significant proportion of young women intentionally tan. Furthermore, we know very little about the family’s role in melanoma-related risk practices. Consequently, this study examined twenty-two interviews of adolescent girls and their mothers discussing topics related to sun protection and tanning behavior. Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…A total of 17 articles reporting 16 studies were included in the meta‐synthesis (see Table 3 ). One study's findings were reported in two articles (Gordon et al, 2016 ; Hay et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 17 articles reporting 16 studies were included in the meta‐synthesis (see Table 3 ). One study's findings were reported in two articles (Gordon et al, 2016 ; Hay et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some users downplayed the risk by considering that the risk was acceptable, for example, tanning was just one of many risky behaviours (Gordon et al, 2016; Lyons et al, 2021; Taylor et al, 2017, 2018); that the media overstated the risks (Lake et al, 2014); or in a minority of cases that the potential effects of skin cancer were insignificant (Lake et al, 2014).
If you've got skin cancer you can get over it quick.(Participant quote) Lake et al (2014) p. 60.
But just about everyone seemed to downplay this risk.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation